Expression of the stem cell markers NANOG and SOX2 in the cervical squamous carcinogenesis - Koren Miha; Zlajpah Margareta; Poljak Mario; Komlos Kristina Fujs; Flezar Margareta Strojan (Radiology and Oncology)
The aim of the present study was to assess a diagnostic potential of stem cell markers NANOG and SOX2 for classifying cervical squamous intraepithelial lesions (SILs)/cervical intraepithelial neoplasia (CIN).